Growth effect of public debt: The role of government effectiveness and trade balance - Mindaugas Butkus; Janina Seputiene (Economies, 2018)
A growing number of recent works support the idea of debt threshold level (turning point), above which debt starts reducing economic growth. However, estimated threshold varies sharply across studies and gives a little insight into what the optimal level of debt is. The point is that there is no single turning point that could be applied to all countries and a proper investigation is needed on factors, which shape the debt impact on growth. This study aims to investigate whether debt threshold level depends on government effectiveness (one of the aspects of countries' institutional quality) and trade balance. Our SYS-GMM estimates (and alternatively OLS and LSDV for robustness check) are based on the unbalanced panel of 152 countries over the period of 1996-2016 and on two strategies: (i) splitting of sample into subsamples according to trade balance and government effectiveness and (ii) including debt and government effectiveness, debt and trade deficit interactions. The obtained results are in line with those which confirm inverted U-shaped debt-growth relationship with clear debt turning point dependence on government effectiveness. However, effective governance is not enough to avoid the negative debt effect. Trade balance seems to be more crucial factor than institutional quality, on which threshold level depends.
Keywords: C23; F34; F40; O43; 330; public debt; economic growth; government effectiveness; trade balance; panel estimates